Antioxidant Analysis of Kawa Daun (Coffea canephora) Beverage by In Vitro and In Silico Approaches - Ifwarisan Defri; Nurheni Sri Palupi; Setyanto Tri Wahyudi; Nancy Dewi Yuliana (Indonesian Journal of Chemistry, 2022)
In Tanah Datar Regency, West Sumatra, Indonesia, the waste of pruning coffee leaves (Coffea canephora) is utilized as a traditional beverage called "Kawa Daun". For a consistent quality of Kawa Daun functional beverage, we evaluated the effect of different smoking times (0, 2, 4, and 6 h) on its in vitro DPPH antioxidant activity. Estimation of antioxidant components from the coffee leaf was conducted in silico using Peroxiredoxin V (PrxV) with 3MNG code as a receptor, and 33 phytochemicals were reported to be present in the coffee leaves as ligands. As a result, Kawa Daun, with a 2-h smoking time, had the highest antioxidant activity. Molecular docking between PrxV and the 33 compounds resulted in the ten most potential compounds based on the affinity energy. They were xanthone (-4.9 kcal/mol), uric acid (-4.8 kcal/mol), xanthosine (-4.8 kcal/mol), caffeine (-4.6 kcal/mol), 3-methylxanthine (-4.6 kcal/mol), 7-methylxanthosine (-4.6 kcal/mol), theobromine (-4.5 kcal/mol), theophylline (-4.5 kcal/mol), caffeic acid (-4.5 kcal/mol), and xanthine (-4.4 kcal/mol). These ten ligands had stronger interactions than the control ligand 1.2-dithiane-4.5-diol (-3.6 kcal/mol). This research showed the potential of Kawa Daun as a functional beverage with antioxidant activity. Further confirmation on the antioxidant potential of this beverage using an in vivo method is recommended.